Metaphor in the Selected Song Lyrics of Lana Del Rey (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2025)
This study analyzes the use of metaphors in Lana Del Rey's song lyrics with a focus on their types and meanings based on Lakoff and Johnson's (1980) conceptual metaphor theory and Leech's (1981) meaning theory. The three main metaphor types identified are structural, orientational, and ontological metaphors, each of which conveys themes such as nostalgia, love, rebellion, and identity. Examples of metaphors found include images of life as art, nostalgia as an aging star, and love that transcends youth. This study highlights how Lana Del Rey uses metaphors to express complex emotions and cultural values, thus enriching the understanding of her lyrical themes. In addition, the use of ontological metaphors in the songs depicts deep emotional, spiritual, and psychological experiences through certain symbols such as heaven, favorite sweater, and red dress, which enriches the connotative meaning of the lyrics.